1975
DOI: 10.1073/pnas.72.10.4018
|View full text |Cite
|
Sign up to set email alerts
|

New approach to antifolate treatment of certain cancers as demonstrated in tissue culture.

Abstract: The selective toxicity of antifolates for a variety of cancers can be improved, as illustrated by the combined administration of N0-methyltetrahydrofolate and methotrexate in tissue culture. When a variety of neoplastic cell types characterized by a deficiency of vitamin flisdependent N5-methyltetrahydrofolate methyltransferase (5- (18,19). It is clear that very specific "C1"-carrying tetrahydrofolates are uniquely required for the synthesis of thymidylic acid and the de novo synthesis of purines. The need fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

1977
1977
1997
1997

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 39 publications
0
5
0
1
Order By: Relevance
“…Studies of this kind could lead to a better understanding of the biochemical basis of the megaloblastic anemia and neurologic defects associated with Cbl deficiency, as well as to the development of a new class of chemotherapeutic agents for malignancies. Investigation of the latter possibility appears particularly interesting since several recent studies (44,45) indicate that a number of malignant cell lines differ from normal cells in terms of their activities of, and/or their dependence on, the Cbl-dependent enzyme methionine synthetase which catalyzes the conversion of N5-methyltetrahydrofolate and homocysteine to tetrahydrofolate and methionine.…”
Section: Resultsmentioning
confidence: 99%
“…Studies of this kind could lead to a better understanding of the biochemical basis of the megaloblastic anemia and neurologic defects associated with Cbl deficiency, as well as to the development of a new class of chemotherapeutic agents for malignancies. Investigation of the latter possibility appears particularly interesting since several recent studies (44,45) indicate that a number of malignant cell lines differ from normal cells in terms of their activities of, and/or their dependence on, the Cbl-dependent enzyme methionine synthetase which catalyzes the conversion of N5-methyltetrahydrofolate and homocysteine to tetrahydrofolate and methionine.…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, there have been only a limited number of studies on the mechanisms of MTX resistance in various mammalian cell lines using a reduced form of folate as a source of folate in the medium during the development of resistance. Most studies were not designed to investigate the effect of the form of folate derivative on the mechanism of development of MTX resistance (Hakala et al ., 1961; Halpern et al ., 1975; van der Veer et al ., 1989; Jansen et al ., 1990; van der Laan et al ., 1991a, b; Houghton et al ., 1992; Miyachi et al ., 1992).…”
Section: Discussionmentioning
confidence: 99%
“…6, an FBP Halpern et al, 1975;van der Veer et al, 1989;Jansen et al, 1990;van der Laan et al, 1991a, b;Houghton et al, 1992;Miyachi et al, 1992).…”
Section: Folate-binding Proteinunclassified
“…Among various theories on the rationale for the selective effectiveness of the high-dose MTX regimen with LV rescue (19), the one proposed by Halpern et al (20) based on their study using a tissue culture system is very interesting. They found that when a variety of neoplastic cell types characterized by a deficiency of vitamin B12-dependent MTHF methyltransferase and normal adult cells was grown in media containing MTX and with either MTHF or FTHF, not only was the selective toxicity of MTX demonstrated but the advantage of using MTHF in place of FTHF also revealed.…”
Section: Discussionmentioning
confidence: 99%